Formulation of Gel HandSanitizer Ethanol Extract Salam Leaves with Carbopol and Na CMC as Gelling Agent - Cory Linda Futri; Hasni Yaturramadhan (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
Hand sanitizer gel has been widely used as a way to maintain hand health and hygiene that is practical and easy to carry. Generally hand sanitizer gels contain alcohol compounds as antiseptics to kill bacteria, but the use of antiseptic gels that contain alcohol in the long term can cause irritation. Therefore, we need natural alternative materials that are friendly to the skin and do not irritate the skin, one of the plants that has antibacterial power is bay leaf (Syzygium polyanthum). The purpose of this study was to determine the formulation and physical properties of hand sanitizer gel from bay leaf extract (Syzygium polyanthum). This research is an experimental study with research data presented descriptively. The gel was made in three formulas with different carbopol concentrations, namely 0.2%, 0.5%, and 3% Na CMC. The evaluation of the physical properties of the gel included organoleptic, homogeneity, dispersibility, adhesion, and pH tests. The results of the evaluation showed that formula 1 (Na CMC 3%, ethanolic extract of bay leaf 12.5%) and formula 2 (carbopol 0.2%, ethanolic extract of bay leaf 12.5%) fulfilled all the requirements for evaluating the physical properties of the gel which included organoleptic test, homogeneity, spreadability, adhesion, and pH. While formula 3 (carbopol 0.8%, ethanol extract of bay leaf 25%) did not meet the physical properties test, namely the dispersion test.